Islamic Financial Management Behavior Mediates Sharia Financial Literacy and Investment Behavior - Ardiansyah, Ardiansyah; Hamzah, Aksi; Karyono, Otong (Equilibrium: Jurnal Ekonomi Syariah, 2024)
The main objective of this research is to contribute to the literature by focusing on the relationship between Islamic financial literacy and investment behavior while identifying the mediating effect of Islamic financial management behavior among millennial generations. This study adopts a quantitative research design. Data for this research were obtained through the distribution and completion of questionnaires by millennials in South Sulawesi. The questionnaire distribution took place over a span of 3 months (September-October 2023). The population in this study consists of millennials in South Sulawesi, and the sampling technique employed is purposive sampling. SmartPLS version 4 is utilized as the data analysis tool. The results of the research show that Sharia financial literacy has a positive and significant effect on Islamic financial management behavior, Islamic financial management behavior has a positive and significant effect on investment behavior, Islamic financial management behavior has a positive and significant effect in mediating the relationship between sharia financial literacy and investment behavior, and sharia financial literacy has no effect on investment behavior.